2018
DOI: 10.1016/j.molcel.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Fidelity of the Repair of Cas9-Induced Double-Strand DNA Breaks

Abstract: SummaryThe RNA-guided DNA endonuclease Cas9 is a powerful tool for genome editing. Little is known about the kinetics and fidelity of the double-strand break (DSB) repair process that follows a Cas9 cutting event in living cells. Here, we developed a strategy to measure the kinetics of DSB repair for single loci in human cells. Quantitative modeling of repaired DNA in time series after Cas9 activation reveals variable and often slow repair rates, with half-life times up to ∼10 hr. Furthermore, repair of the DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
263
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(280 citation statements)
references
References 59 publications
17
263
0
Order By: Relevance
“…A crude estimate from Kim et al 29 suggested that indel formation by CRISPR/Cas occurs early in the process but is detected only after about fifteen hours. These data align with the belief that sequence specific nucleases direct indel formation only after multiple cycles of breakage and perfect repair 11 . Our data suggest that the time delay between penetration of the nucleus and detectable gene editing activity centers around four to eight hours, an observation that aligns with those made by Reid et al 30 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A crude estimate from Kim et al 29 suggested that indel formation by CRISPR/Cas occurs early in the process but is detected only after about fifteen hours. These data align with the belief that sequence specific nucleases direct indel formation only after multiple cycles of breakage and perfect repair 11 . Our data suggest that the time delay between penetration of the nucleus and detectable gene editing activity centers around four to eight hours, an observation that aligns with those made by Reid et al 30 .…”
Section: Discussionsupporting
confidence: 84%
“…Recent data suggest that a time lag exists between nuclear penetration and the appearance of gene editing activity in human cells 11 . For clinical implementation, it is essential that a biological time frame in which the complex enters the cell, penetrates the nuclease and executes its gene editing function is established.…”
Section: Introductionmentioning
confidence: 99%
“…If a suitable template is provided, the cell can use homology-directed repair to integrate a novel allele or transgene at the targeted site (Ceasar, Rajan, Prykhozhij, Berman, & Ignacimuthu, 2016). Alternately, the cell can repair the lesion via nonhomologous end joining (NHEJ), an error-prone process that commonly results in an insertion or deletion (indel) mutation at the DSB location (Brinkman et al, 2018). In this way, CRISPR can be used to introduce stable, nonrevertible alterations to mammalian genes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Cas9 applications concern the cutting of one or both DNA strands within a gene body (Ran et al, 2013). Once the Cas9 protein can cause a nick or a double strand brake that is erroneously repaired by the DNA repair machinery, presence of Cas9 at the locus is neither necessary nor likely anymore (Brinkman et al, 2018). The story is however different for the activator VPR-dCas9.…”
Section: 5mentioning
confidence: 99%